Pertumbuhan dan Hasil Tanaman Pakchoy Pada Tanah Berpasir Dengan Pemberian Biochar dan Pupuk Kandang Sapi - Eva Aprilia Saesarini Pangaribuan; Adriani Darmawati; Susilo Budiyanto (Universitas Sebelas Maret, 2020)
Sandy soil is very difficult to remain the water and nutrients so that leaching often occurs before nutrients absorbed by the roots. It can be happen because sandy soil has many macro pores in the soil. This research was aimed to study the effect of biochar and cow manure fertilizer for growth and products of Brassica rapa L. plants on sandy soil. The method used was factorial completely randomized design with 2 factors. This first factor was type of biochar (paddy husk biochar and corn cobs biochar) and the second factor was dosage of cow manure fertilizer (5 tons/ha, 10 tons/ha, 15 tons/ha, 20 tons/ha, 25 tons/ha). The result showed that the application of cow manure fertilizer had significant effected on bulk density and soil porosity. The interaction between the type of biochar and dosage of cow manure fertilizer had significant effect on ground water content. The application of biochar and high doses of cow manure fertilizer resulted in increased ground water content on sandy soil. The type of biochar and dosage of cow manure fertilizer had no significant effect on the nitrogen uptake, plant height, number of leaves, and crown fresh weight.